Policing welfare : punitive adversarialism in public assistance - Headworth, Spencer (Chicago : The University of Chicago Press, 2021)
'Government assistance in the United States requires that recipients meet certain criteria and continue to maintain their eligibility so that benefits are paid to the'truly needy.' Welfare is regarded with such suspicion in this country that considerable resources are spent to police the boundaries of eligibility. Even minor infractions of the many rules can cause people to be dropped from these programs. In this book Spencer Headworth gives us the first study of the structure of fraud control in the welfare system, the relations between different levels of governmental agencies, from federal to local, and their enforcement practices. Policing Welfare shows how the enforcement regime of welfare is trained on those living in poverty furthering their stigmatization and often deepening racial disparities in our society'--
The strings attached -- One nation, finding fraud -- The mill and the grist -- The welfare police -- Occupational frames and identities in fraud control work --Fraud control as performance -- The blame game -- Finding welfare rule violators -- Conclusion.
Includes bibliographical references (pages 267-286) and index.
Keywords: Welfare fraud investigation -- United States; Welfare fraud investigation -- United States -- Case studies; Welfare fraud -- United States; Law enforcement -- United States